Ecological modernisation, environmental innovation and competitiveness: the case of public transport in Hong Kong. (18th November 2005) - Lam, Jacqueline; Hills, Peter; Welford, Richard
This paper focuses on the role of environmental innovation in the context of the development of ecological modernisation theory and as a driver for firms to gain competitive advantage in the market. While ecological modernisation theory offers a variety of theoretical and prescriptive viewpoints on the mechanisms through which modern societies respond to the environmental risks of industrialism, only limited attention has been given to issues of technological innovation and their implications for company competitiveness. Using the public transport sector in Hong Kong as a case study, this paper explores how transport operators have deployed environmental innovation as a means of enhancing their competitive position in the market thereby helping also to address significant local environmental concerns.